Hepatitis B associated with severe COVID-19: a nationwide cohort study in Sweden - Frida Jakobsson; Osvaldo Fonseca-Rodríguez; Hanna Jerndal; Sebastian Kalucza; Soo Aleman; Marie Eriksson; Anne-Marie Fors Connolly (Virology Journal)
Abstract Purpose Individuals with severe liver disease are more vulnerable to severe COVID-19, but the association between chronic hepatitis B virus (HBV) infection and severe COVID-19 remains unclear. This study evaluates this relationship. Methods We analysed nationwide Swedish data from national databases and healthcare registers, identifying laboratory-confirmed COVID-19 cases from February 2020 to April 2021. Chronic HBV infection was classified into cases with and without cirrhosis. Multivariable logistic regression assessed the association between HBV and severe COVID-19, adjusting for demographics, comorbidities, vaccination, and socioeconomic factors. Results Among 1,057,174 COVID-19 cases, 2,902 had chronic HBV infection, which was associated with increased risk of severe COVID-19 (adjusted odds ratio [aOR] 1.242, 95% confidence interval [CI] 1.097–1.403). This risk was significantly higher in HBV individuals with cirrhosis (aOR 2.463, CI 1.546–3.892) compared to those without cirrhosis (aOR 1.183, CI 1.039–1.343). While overall COVID-19 mortality was not significantly elevated in the HBV cohort, patients with cirrhosis showed a higher, though nonsignificant, mortality risk (aOR 2.350, CI 0.921–5.203). Conclusion This nationwide study highlights an increased risk of severe COVID-19 in individuals with chronic HBV, particularly those with cirrhosis. Geographic and socioeconomic factors further influence outcomes. These findings underscore the need to consider HBV status in COVID-19 risk assessments. Future studies should explore these associations in the context of evolving SARS-CoV-2 variants and widespread vaccination.